The Effect of Snand Bottle Load Exercise on the Ability of Badminton Backhand Service of Extracurricular Students of SMP Negeri 63 Bengkulu Utara - Defliyanto; Sugiyanto; Panji Alfian (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine the effect of sand bottle weight training on the badminton backhand serving ability of extracurricular students at SMP Negeri 63 Bengkulu Utara. The research method used was the experimental pre-experimental design (one-group pretest-posttest design) with the independent variable being the sand bottle load and the dependent variable being the ability to serve badminton backhand. The sample in this study consisted of 30 badminton extracurricular students at SMP Negeri 63 Bengkulu Utara. The statistical analysis used is the t test. The results of the t-test analysis for comparison calculations between the final results of the same group subjects, it turns out that there is a significant difference in the sand bottle weight training to the backhand serve